2012
DOI: 10.1007/s00262-011-1178-0
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic adenocarcinoma induces bone marrow mobilization of myeloid-derived suppressor cells which promote primary tumor growth

Abstract: Purpose Myeloid derived suppressor cells (MDSC) are a heterogeneous population of immunosuppressive cells that are upregulated in cancer. Little is known about the prevalence and importance of MDSC in pancreas adenocarcinoma (PA). Experimental Design Peripheral blood, bone marrow, and tumor samples were collected from pancreatic cancer patients, analyzed for MDSC (CD15+CD11b+) by flow cytometry, and compared to cancer free controls. The suppressive capacity of MDSC (CD11b+Gr-1+) and the effectiveness of MDSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
222
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(232 citation statements)
references
References 70 publications
9
222
1
Order By: Relevance
“…S1D). Activity in the aggressive Pan02 model was modest but comparable to the best response observed with standard-of-care cytotoxic agent gemcitabine (37) or immunomodulating agents (38). Tumor growth and tumor-induced immunosuppression is multifactorial and single-agent therapies are unlikely to be curative, but RG7212 monotherapy activity and lack of toxicity suggest that combination therapies should be explored.…”
Section: Anti-tweak Mab Propertiesmentioning
confidence: 99%
“…S1D). Activity in the aggressive Pan02 model was modest but comparable to the best response observed with standard-of-care cytotoxic agent gemcitabine (37) or immunomodulating agents (38). Tumor growth and tumor-induced immunosuppression is multifactorial and single-agent therapies are unlikely to be curative, but RG7212 monotherapy activity and lack of toxicity suggest that combination therapies should be explored.…”
Section: Anti-tweak Mab Propertiesmentioning
confidence: 99%
“…In PDAC, MDSC infiltrations are observed as early as the preinvasive PanIN lesions and progressively increase throughout the evolution of the tumor (Clark et al 2007;Zhao et al 2009;Zhang et al 2014b). G-CSF and GM-CSF (Bayne et al 2012;Pylayeva-Gupta et al 2012); IL-3, M-CSF, and IL-6 (Serafini et al 2006); and CCL2 chemokine (Tjomsland et al 2011) have been shown to be released by PDAC cancer cells to promote MDSC recruitment to the tumor microenvironment (Porembka et al 2012) and suppress antigen-specific T cells. G-CSF and GM-CSF expression is driven by oncogenic KRAS via the RAS/MEK/MAPK pathway through the ETS transcription factor (Bayne et al 2012); correspondingly, MEK or PI3K inhibitors can attenuate the release of G-CSF and improve survival in an orthotopic allograft mouse model established by injecting primary ductal epithelial cells (PDECs) isolated from a GEMM of PDAC into the pancreata of syngeneic C57Bl/6 mice (Cox and Olive 2012;Pylayeva-Gupta et al 2012).…”
Section: Mdscs and Tamsmentioning
confidence: 99%
“…Another type of tumorassociated immune cell that has gained a lot of recent attention is the myeloid-derived suppressor cell (MDSC) [51,52]. MDSCs represent a heterogeneous group of immature [198][199][200].…”
Section: Box 2: Immune Complexity In Tumor-bearing Hostsmentioning
confidence: 99%